STUDI PRAGMATIS PERKARA PERDATA NOMOR 757/Pdt.G/2022/PN Jkt.Pst: IMPLIKASI PENUNDAAN PEMILU - Hisyamsyah Yuditomo; Ismawati Septiningsih (Verstek, 2025)
This article analyzes related to the pragmatic study of civil case Pragmatic Study of Civil Case Number 757/Pdt.G/2022/PN Jkt.Pst: Implication of Election Delay. The purpose of this article is to determine the impact and absolute authority of the issuance of the civil decision. The issue is analyzed using normative research using primary legal materials and secondary legal materials. The approaches used in this article include a conceptual approach and a case study approach. The conceptual approach focused on a pragmatic study of the civil decision. The results show that there is a legal defect, namely that disputes related to the results of verification of political parties participating in the election are not the absolute authority of the District Court, but rather the authority of the Election Supervisory Agency (Bawaslu) and the State Administrative Court in accordance with the provisions in Law Number 7 of 2017. In addition, lawsuits related to unlawful acts are now also included in the scope of authority of the State Administrative Court asm stipulated in Supreme Court Regulation Number 2 of 2019.